Cancer Risk Assessment Using Genetic Panel Testing: Considerations for Clinical Application. Issue 4 (7th March 2014) - Hiraki, Susan; Rinella, Erica S.; Schnabel, Freya; Oratz, Ruth; Ostrer, Harry
Abstract: With the completion of the Human Genome Project and the development of high throughput technologies, such as next‐generation sequencing, the use of multiplex genetic testing, in which multiple genes are sequenced simultaneously to test for one or more conditions, is growing rapidly. Reflecting underlying heterogeneity where a broad range of genes confer risks for one or more cancers, the development of genetic cancer panels to assess these risks represents just one example of how multiplex testing is being applied clinically. There are a number of issues and challenges to consider when conducting genetic testing for cancer risk assessment, and these issues become exceedingly more complex when moving from the traditional single‐gene approach to panel testing. Here, we address the practical considerations for clinical use of panel testing for breast, ovarian, and colon cancers, including the benefits, limitations and challenges, genetic counseling issues, and management guidelines.